2022
DOI: 10.3390/ph15070779
|View full text |Cite
|
Sign up to set email alerts
|

Novel Therapies to Address Unmet Needs in ITP

Abstract: Primary immune thrombocytopenia (ITP) is an autoimmune disorder that causes low platelet counts and subsequent bleeding risk. Although current corticosteroid-based ITP therapies are able to improve platelet counts, up to 70% of subjects with an ITP diagnosis do not achieve a sustained clinical response in the absence of treatment, thus requiring a second-line therapy option as well as additional care to prevent bleeding. Less than 40% of patients treated with thrombopoietin analogs, 60% of those treated with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 118 publications
0
8
0
Order By: Relevance
“…A phase III trial NCT05029635 is in progress to further assess the safety and efficacy of HMPL-523 in patients with refractory ITP. It can be used as an alternative agent to fostamatinib for SYK inhibition [ 27 , 28 ]. The drug is not yet approved by FDA and is not available in the market for ITP.…”
Section: Discussionmentioning
confidence: 99%
“…A phase III trial NCT05029635 is in progress to further assess the safety and efficacy of HMPL-523 in patients with refractory ITP. It can be used as an alternative agent to fostamatinib for SYK inhibition [ 27 , 28 ]. The drug is not yet approved by FDA and is not available in the market for ITP.…”
Section: Discussionmentioning
confidence: 99%
“…Elucidating the mechanisms underlying ITP and designing novel therapies to address the current care gap continue to be active areas of research that are reviewed in detail elsewhere. 12,15,56 A growing number of therapies with various mechanisms of action are being investigated in latephase clinical trials, with expected readouts within journals.sagepub.com/home/tah TherapeuTic advances in hematology the next 5 years. Among emerging therapeutic agents developed for ITP, the putative mechanisms of action of rilzabrutinib in ITP are thought to target both immune-mediated platelet destruction through blocking FcR-mediated platelet destruction and inhibition of platelet production, and by reducing the level of pathogenic antiplatelet antibodies due to suppression of autoreactive B cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, splenectomy might be associated with short-term surgery-related complications and long-term increased risks of thrombosis and infection. 14,15 The disease burden is more significant in patients with severe and chronic thrombocytopenia requiring ongoing treatment and those who are unresponsive to current therapy, contributing to elevated mortality rates relative to the general population. 16,17 Adult patients with chronic thrombocytopenia have up to a 10% risk of bleeding or hemorrhage that increases with age, and intracranial hemorrhage has been reported in ~1-2% of patients.…”
Section: Immune Thrombocytopeniamentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found that both Cluster of Differentiation 8 + (CD8 + ) T cells and Cluster of Differentiation 4 + (CD4 + ) T cells with antiplatelet reactivity are found in peripheral blood. CD8 + T cells can inhibit B lymphocytes from producing platelet antibodies, while the decrease in the number of CD4 + T cells can make auto reactive B lymphocytes proliferate accordingly, thereby producing some antibodies that promote platelet destruction [5][6][7] , indicating that T lymphocytes can regulate platelet antibody production. The immune response of T lymphocytes may be another mechanism that causes immune PTR, but there are few studies on the regulation mechanism of T lymphocytes on immune PTR.…”
mentioning
confidence: 99%